PENDEKATAN BIMBINGAN KONSELING ISLAM DI SMK NEGERI 1 PANYABUNGAN - Pohan, Ali Jusri; Pulungan, Alfiani; Nasution, Alfina; Rizkilah, Hilda; Mulia, Mahdi; Riski, Nanda Mulia; Jannah, Nur (Penerbit Widina, Widina Media Utama, 2024)
The importance of counseling in schools cannot be overstated, as it plays a vital role in improving students' academic and personal well-being. Individual Counseling Guidance (BKI), a type of individual counseling, is increasingly recognized as an important component in comprehensive school counseling programs. Even though it has potential benefits, the application of BKI in schools in Indonesia is still limited. This research aims to explore the application of a student-centered approach at SMKN 1 Panyabungan. A student-oriented approach emphasizes student autonomy, participation, and involvement in the learning process. In this research, the author used a qualitative research design. This methodology involves observations, interviews, and focus group discussions with students, teachers, and administrators. The findings of this research indicate that schools have made various efforts to move from a traditional teacher-centered approach to a more student-centered approach. Here, students are encouraged to take 'ownership' of their learning - through project-based learning, problem-solving activities and technology integration. Teachers have also taken on new roles as facilitators and mentors, willing to guide and support when needed. The results of the study stated that students reported that they felt clearly more motivated, more involved in learning, and more satisfied. Moreover, teachers feel more satisfied with their work and feel like they have achieved something. This study emphasizes how important it is for teachers to receive continuous education at a professional level. Schools are also expected to provide appropriate equipment and support resources for implementing a student-centered approach..ABSTRAKPentingnya konseling di sekolah tidak bisa dilebih-lebihkan, karena konseling memainkan peran penting dalam meningkatkan kesejahteraan akademis dan pribadi siswa. Bimbingan Konseling Individu (BKI), salah satu jenis konseling individu, semakin dikenal sebagai komponen penting dalam program konseling sekolah yang komprehensif. Meskipun mempunyai potensi manfaat, penerapan BKI di sekolah-sekolah di Indonesia masih terbatas. Penelitian ini bertujuan untuk mengeksplorasi penerapan pendekatan yang berpusat pada siswa di SMKN 1 Panyabungan. Pendekatan yang berorientasi pada siswa menekankan otonomi, partisipasi, dan keterlibatan siswa dalam proses pembelajaran. Dalam penelitian ini, penulis menggunakan desain penelitian kualitatif. Metodologi ini melibatkan observasi, wawancara, dan diskusi kelompok terfokus dengan siswa, guru, dan administrator. Temuan dari penelitian ini menunjukkan bahwa sekolah telah melakukan berbagai upaya untuk beralih dari pendekatan yang tradisional yang berpusat pada guru ke pendekatan yang lebih berpusat pada siswa. Di sini, siswa didorong untuk mengambil 'kepemilikan' atas pembelajaran mereka - melalui pembelajaran berbasis proyek, aktivitas pemecahan masalah, dan integrasi teknologi. Guru juga telah mengambil peran baru sebagai fasilitator dan mentor, yang bersedia membimbing dan mendukung bila diperlukan. Atas hasil studi itu dinyatakan bahwa siswa melaporkan bahwa mereka merasa jelas lebih termotivasi, lebih terlibat dalam pembelajaran, serta lebih puas. Apalagi, guru merasa lebih puas dengan pekerjaan mereka dan merasa sudah mencapai sesuatu. Studi ini menekankan betapa pentingnya bagi guru untuk mendapat pendidikan yang terus menerus pada tingkat profesional. Sekolah juga diharapkan dapat menyediakan peralatan dan sumber-sumber dukungan yang layak bagi penerapan pendekatan yang berpusat pada siswa.